Effects of autolytical fish protein hydrolysate on growth performance, survival rate, and hematological indices in farmed juvenile beluga, Huso huso - Ali Hosseinpour Zelaty (تغذیه آبزیان)
Introduction: Aquaculture's rapid expansion has led to a high demand for fishmeal, a key protein source in aquafeed. To address this, alternatives like fish protein hydrolysates (FPHs) are being investigated. FPHs are produced from the enzymatic digestion of proteins in fish processing waste. They have been found to enhance fish growth, feed efficiency, immune responses, and disease resistance. FPHs contain functional and bioactive peptides, making them a viable substitute for fishmeal in aquafeeds. They are also a rich source of proteins, amino acids, peptides, and antioxidants, which are beneficial for fish health and welfare. However, it is important to determine the optimal FPH inclusion level to avoid potential negative effects from excessive use. This study investigates the effects of different levels of autolytical FHP on the growth performance, survival, and some blood parameters of juvenile beluga, Huso huso over a 48-day period. Materials and methods: A total of 750 belugas with an initial weight of 3 ± 0.5 g were randomly distributed into five experimental groups: a control group (without FHP), three treatments with different levels of FHP replacing fishmeal (T1, T2, and T3 with inclusion level of 2.75%, 5.5%, and 8.25%, respectively), and a positive control group (commercial feed, T4). The experiment was carried out in 15 tanks (500-L), each containing 50 fish. The inflow water rate was 2 L/min, and the water exchange rate was 6 to 7 times per day in each tank. The fish's growth performance was evaluated by measuring its biometric characteristics every 15 days. Hematological parameters were assessed by collecting blood samples from the treatment and control groups at the end of the study. Results: The results indicated that the beluga fed the experimental diets containing FHP had higher survival rates than the control group. The growth indices in the FHP treatments were higher than those in the control group, however, the differences were not statistically significant (p>0.05). Analyses of hematological parameters showed no significant difference in white blood cell count between treatments 1, 2, 3 and the control group (p>0.05). However, in treatment 4 it was significantly different from all other groups (p<0.05). The red blood cell (RBC) count of the control group was significantly different from that of T1 (p<0.05), with the highest RBC observed in T1. There were no significant differences in neutrophil percentages between the control group and T1 and T3. Additionally, T2 and T3 did not differ significantly from each other (p>0.05). However, T4 showed a significant difference in neutrophil percentage compared to the other treatments (p<0.05). In addition, T4 exhibited the lowest lymphocyte percentage, which was significantly different from the other groups (p<0.05). No significant differences were found between the experimental groups in other blood parameters, such as hemoglobin, hematocrit, red blood cell indices, monocyte and eosinophil percentages (p>0.05). Discussion: The present study showed that dietary supplementation of hydrolyzed protein in juvenile beluga diet significantly improved survival and growth performance (final weight, specific growth rate and daily growth rate) and did not induce any adverse alterations in the measured blood indices compared to the control group. FPH, derived from enzymatic hydrolysis of fish waste, is rich in proteins, amino acids, peptides, and antioxidants, and contains functional and bioactive peptides. These components can improve growth, feed utilization and immune functions in fish. It seems that optimal levels of FPH supplementation can enhance juvenile beluga growth and health by providing a balanced amino acid profile and bioactive substances that support physiological responses. Conclusion: In conclusion, the present study demonstrated that the replacement of fishmeal with hydrolyzed protein up to level of 8.25% resulted in increased survival and improved growth performance of juvenile beluga compared to the control group, without any adverse effects on blood indices.